A Novel Hybrid Hand Instrumentation Technique for Root Canal Preparation - Bolourchi, Iman; Pourmousavi, Leila (Iranian Endodontic Journal, 2018)
Introduction: Preparation of root canal system necessitates both enlargement and shaping of the complex root canal space together with disinfection of the easily accessible and hidden areas. The present article introduces a new manual root canal preparation technique and compares it with passive step-back and step-back regarding some items such as shaping efficacy, maintenance of working length and occurrence of procedural accidents. Methods and Materials: This canal preparation technique (Bolourchi Hybrid Technique-BHT) was compared with passive step-back and step-back root through preparation of 30 extracted human mandibular and maxillary molars. Three experienced endodontists evaluated the final radiographies for following items: 1) difficulty of the case 2) shaping efficacy 3) maintenance of working length 4) time of preparation. Two-way ANOVA was used to analyze the data. Multiple comparisons were done using the Tukey’s HSD. Results: Regarding shaping efficacy and maintenance of working length, BHT group showed significantly higher scores and scores for step-back group were significantly the lowest. The difference between BHT group and passive step-back on these items was not significant. No significant differences were found between the techniques in other assessed criteria except for occurrence of procedural accidents which was significantly higher in step-back group. Conclusion: Considering the advantages of this novel technique as well as its comparability to the present routine techniques, it can be considered as an available root preparation technique for teaching in dental schools. Keywords:Balanced Forced Technique; Hand Instrumentation; Hybrid Hand Instrumentation; Passive Step-Back; Root Canal Preparation; Step-Back